Longitudinal Analysis of Antibody Responses to the mRNA BNT162b2 Vaccine in Patients Undergoing Maintenance Hemodialysis: A 6-Month Follow-Up - Weigert, André; Bergman, Marie-Louise; Gonçalves, Lígia A.; Godinho, Iolanda; Duarte, Nádia; Abrantes, Rita; Borges, Patrícia; Brennand, Ana; Malheiro, Vanessa; Matoso, Paula; Akpogheneta, Onome; Kosack, Lindsay; et al. (Frontiers in Medicine, 2021)
Background: Patients on hemodialysis (HD) are at higher risk for COVID-19, overall are poor responders to vaccines, and were prioritized in the Portuguese vaccination campaign. Objective: This work aimed at evaluating in HD patients the immunogenicity of BTN162b2 after the two doses induction phase, the persistence of specific antibodies along time, and factors predicting these outcomes. Methods: We performed a prospective, 6-month long longitudinal cohort analysis of 156 HD patients scheduled to receive BTN162b2. ELISA quantified anti-spike IgG, IgM, and IgA levels in sera were collected every 3 weeks during the induction phase (t0 before vaccine; t1, d21 post first dose; and t2 d21 post second dose), and every 3–4 months during the waning phase (t3, d140, and t4, d180 post first dose). The age-matched control cohort was similarly analyzed from t0 to t2. Results: Upon exclusion of participants identified as previously exposed to SARS-CoV-2, seroconversion at t1 was lower in patients than controls (29 and 50%, respectively, p = 0.0014), while the second vaccine dose served as a boost in both cohorts (91 and 95% positivity, respectively, at t2, p = 0.2463). Lower response in patients than controls at t1 was a singularity of the participants ≤ 70 years (p = 2.01 × 10−05), associated with immunosuppressive therapies (p = 0.013), but not with lack of responsiveness to hepatitis B. Anti-spike IgG, IgM, and IgA levels decreased at t3, with IgG levels further waning at t4 and resulting in >30% seronegativity. Anti-spike IgG levels at t1 and t4 were correlated (ρ = 0.65, p < 2.2 × 10−16). Conclusions: While most HD patients seroconvert upon 2 doses of BNT162b2 vaccination, anti-spike antibodies levels wane over the following 4 months, leading to early seroreversion in a sizeable fraction of the patients. These findings warrant close monitoring of COVID-19 infection in vaccinated HD patients, and advocate for further studies following reinforced vaccination schedules.